Back Cover: Hydrogen Generation by Water Reduction with [Cp*2Ti(OTf)]: Identifying Elemental Mechanistic Steps by Combined In Situ FTIR and In Situ EPR Spectroscopy Supported by DFT Calculations (Chem. Eur. J. 41/2013). Issue 41 (1st October 2013) - Hollmann, Dirk; Grabow, Kathleen; Jiao, Haijun; Kessler, Monty; Spannenberg, Anke; Beweries, Torsten; Bentrup, Ursula; Brückner, Angelika
<x xml:space="preserve">Abstract</x> Hydrogen evolution from water is a true challenge, yet it is possible with titanium complexes. In their Full Paper on page 13705 ff., D. Hollmann, T. Beweries, A. Brückner et al. unravel the mechanism of water activation and hydrogen formation on decamethyltitanocene triflate by using in situ spectroscopy supported by DFT calculations. The picture relates the flexibility of the titanium ligand sphere with that of a Titanflex® eyeglass frame.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>